Lived experiences with regards to social participation for persons with disabilities living in a residential facility in Cape Town - Hairwadzi, Francisca (Stellenbosch : Stellenbosch University, 2021)
Thesis (MHumanRehabSt)--Stellenbosch University, 2021.